Plasma wakefield acceleration experiments at FACET - Hogan, M; Raubenheimer, T; Seryi, A; Muggli, P; Katsouleas, T; Huang, C; Lu, W; An, W; Marsh, K; Mori, W; Clayton, C; Joshi, C (IOP Publishing, 2010)
FACET-Facilities for Accelerator science and Experimental Test beams at SLAC-will provide high-energy-density electron and positron beams with peak currents of roughly 20 kA that will be focused down to a 10 μm × 10μm transverse spot size at an energy of ∼23 GeV. With FACET, the SLAC linac will support a unique program concentrating on second-generation research in plasma wakefield acceleration. Topics include high-gradient electron acceleration with a narrow energy spread and preserved emittance, beam loading and high-gradient positron acceleration. This paper describes the FACET facility, summarizes the state of the art for plasma wakefield accelerators and discusses the plasma wakefield accelerator program to be conducted at FACET over the next five years. © IOP Publishing Ltd and Deutsche Physikalische Gesellschaft.